Synthesis of (+)-DGDP and (-)-7-epialexine. - Donohoe, T; Cheeseman, MD; O'Riordan, T; Kershaw, J (2008)
The partial reduction of electron deficient pyrroles is an extremely versatile method that allows us to prepare substituted pyrrolidines and pyrrolizidines with trans-diol stereochemistry on the five membered ring.